2013
DOI: 10.1292/jvms.13-0199
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Contrast Enhanced Ultrasonography of the Pancreas Using Bolus Injection and Continuous Infusion Methods in Normal Dogs

Abstract: Quantitative contrast enhanced ultrasound is a major breakthrough for ultrasound imaging in recent years. However, contrast enhancement of the pancreas is brief with bolus injection. To assess if continuous infusion of Sonazoid® can prolong the duration of pancreatic enhancement over bolus injections, eight adult dogs received bolus injection and continuous infusion of Sonazoid® on separate days. Contrast enhanced ultrasound of the pancreatic parenchyma and proximal descending duodenum was performed, and time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 28 publications
(55 reference statements)
3
30
1
Order By: Relevance
“…Time parameters corresponding to blood flow velocity (peak time, wash‐in time, wash‐in to peak time, and time to peak enhancement) and intensity parameters (peak and mean intensity) corresponding to blood volume were recorded from the resulting curves. Peak intensity reflecting maximum contrast enhancement while mean intensity reflects the mean pixel intensity over 60 s. Wash‐in was defined as the time when the intensity increased to 30% of the peak intensity . Each pancreas was assessed subjectively for the presence of peripheral or hilar vessels, speed of wash‐in, wash‐out, and homogeneity of the contrast enhancement.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…Time parameters corresponding to blood flow velocity (peak time, wash‐in time, wash‐in to peak time, and time to peak enhancement) and intensity parameters (peak and mean intensity) corresponding to blood volume were recorded from the resulting curves. Peak intensity reflecting maximum contrast enhancement while mean intensity reflects the mean pixel intensity over 60 s. Wash‐in was defined as the time when the intensity increased to 30% of the peak intensity . Each pancreas was assessed subjectively for the presence of peripheral or hilar vessels, speed of wash‐in, wash‐out, and homogeneity of the contrast enhancement.…”
Section: Methodssupporting
confidence: 92%
“…The typical time‐intensity curve for the healthy pancreas shows a rapid increased followed by a short peak of strong enhancement with a fast wash out . The shape of the time‐intensity curves (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Perfusion of the HV was evaluated after intravenous bolus injection of microbubble contrast agent (Sonazoid ® , Daiichi Sankyo, Tokyo, Japan). According to our previous report [12], we administered 0.01 m l /kg Sonazoid ® through a 21 G butterfly catheter attached to a 22 G intravenous catheter placed in the cephalic vein, flushed by 2 m l of heparinized saline. Immediately after bolus injection, continuous scanning of the right HV was performed for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…In veterinary medicine, two original articles and two review papers have been published on CEUS characteristics of the pancreas in dogs. [14][15][16][17] However, at the time of this study, there were no published studies describing the contrast-enhanced ultrasonographic characteristics of pancreatic insulinomas in dogs. The purpose of this study was to describe CEUS findings for a group of dogs with confirmed pancreatic insulinomas.…”
Section: Introductionmentioning
confidence: 99%